Fluoroscopy of Spontaneous Breathing is More Sensitive Than Phrenic Nerve Stimulation for Detection of Right Phrenic Nerve Injury During Cryoballoon Ablation of Atrial Fibrillation. (18th May 2014) - LINHART, MARKUS; NIELSON, ANNIKA; ANDRIÉ, RENÉ P.; MITTMANN‐BRAUN, ERICA L.; STÖCKIGT, FLORIAN; KREUZ, JENS; NICKENIG, GEORG; SCHRICKEL, JAN W.; LICKFETT, LARS M.
Monitoring of Phrenic Nerve During Cryoballoon Ablation: Introduction: Right phrenic nerve palsy (PNP) is a typical complication of cryoballoon ablation of the right‐sided pulmonary veins (PVs). Phrenic nerve function can be monitored by palpating the abdomen during phrenic nerve pacing from the superior vena cava (SVC pacing) or by fluoroscopy of spontaneous breathing. We sought to compare the sensitivity of these 2 techniques during cryoballoon ablation for detection of PNP. Methods and Results: A total of 133 patients undergoing cryoballoon ablation were monitored with both SVC pacing and fluoroscopy of spontaneous breathing during ablation of the right superior PV. PNP occurred in 27/133 patients (20.0%). Most patients (89%) had spontaneous recovery of phrenic nerve function at the end of the procedure or on the following day. Three patients were discharged with persistent PNP. All PNP were detected first by fluoroscopic observation of diaphragm movement during spontaneous breathing, while diaphragm could still be stimulated by SVC pacing. In patients with no recovery until discharge, PNP occurred at a significantly earlier time (86 ± 34 seconds vs. 296 ± 159 seconds, P < 0.001). No recovery occurred in 2/4 patients who were ablated with a 23 mm cryoballoon as opposed to 1/23 patients with a 28 mm cryoballoon (P = 0.049). Conclusion: Fluoroscopic assessment of diaphragm movement during spontaneous breathing is more sensitive for detection PNP as compared to SVC pacing. PNP as assessed by fluoroscopy is frequent (20.0%) and carries a high rate of recovery (89%) until discharge. Early onset of PNP and use of 23 mm cryoballoon are associated with PNP persisting beyond hospital discharge.